Activos Intangibles y su Importancia (2022)
The research is carried out to highlight the importance of intangibles within variables that influence the company, from globalization, and competitiveness within the markets, forces their managers to find the factors that help achieve the seccess of their companies. The methodology used was the search for articles on intangible assets, to find common points of vie won the importance of intangible assets.